2018 Ottawa consensus statement: Selection and recruitment to the healthcare professions. (2nd November 2018) - Patterson, F.; Roberts, C.; Hanson, M. D.; Hampe, W.; Eva, K.; Ponnamperuma, G.; Magzoub, M.; Tekian, A.; Cleland, J.
Abstract: Selection and recruitment into healthcare education and practice is a key area of interest for educators with significant developments in research, policy, and practice in recent years. This updated consensus statement, developed through a multi-stage process, examines future opportunities and challenges in selection and recruitment. There is both a gap in the literature around and a compelling case for further theoretical and empirical literature to underpin the development of overall selection philosophes and policies and their enactment. More consistent evidence has emerged regarding the quality of different selection methods. Approaches to selection are context-dependent, requiring the consideration of an institution's philosophy regarding what they are trying to achieve, the communities it purports to serve, along with the system within which they are used. Diversity and globalization issues continue to be critically important topics. Further research is required to explore differential attainment and explain why there are substantial differences in culturally acceptable ways of approaching diversity and widening access. More sophisticated evaluation approaches using multi-disciplinary theoretical frameworks are required to address the issues. Following a discussion of these areas, 10 recommendations are presented to guide future research and practice and to encourage debate between colleagues across the globe.